2022
DOI: 10.9734/arrb/2022/v37i1230560
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Study of TCF7L2 Gene Mutation on Insulin Secretion for Type 2 DM Patients: A Review

Abstract: Aim: This paper aims to establish whether a correlation between TCF7L2 gene mutation on insulin secretion for Type 2 DM Patients. Background: Diabetes type 2 is the most common metabolic disorder worldwide. Beta cell dysfunction reduces insulin secretion and increases the glucose level in the blood and insulin resistance that raises the glucose production in the liver and decreases the glucose uptake to muscle, liver, and adipose tissue causing hyperglycemia (T2DM). TCF7L2 (transcription factor 7–like 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…A study on T2DM patients from the Khyber Pakhtunkhwa population showed a significant risk of T allele either in heterozygote or homozygous state [19]. Similar studies on African, Asian, and Brazilian subjects have reported a strong association of the SNP to T2DM [20].…”
Section: Discussionmentioning
confidence: 74%
“…A study on T2DM patients from the Khyber Pakhtunkhwa population showed a significant risk of T allele either in heterozygote or homozygous state [19]. Similar studies on African, Asian, and Brazilian subjects have reported a strong association of the SNP to T2DM [20].…”
Section: Discussionmentioning
confidence: 74%